Uganda : Third Review Under the Policy Support Instrument and Request for Waiver and Modification of Assessment Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2008)
This paper discusses key findings of the Third Review Under the Policy Support Instrument for Uganda. All end-December 2007 assessment criteria were met. Macroeconomic performance remains strong and the growth outlook remains positive. IMF staff supports the authorities' request for waivers of nonobservance of four structural assessment criteria for end-May and end-June 2008. Nonobservance of these assessment criteria was largely owed to changes in program design in light of new information and reassessment of costs and priorities that do not compromise the integrity of the program.